Diversity, Knowledge, and Use of Plants in Traditional Treatment of Diabetes in the Republic of Benin - Laleye, Fernand Obafemi Arnauld; Mensah, Sylvanus; Assogbadjo, Achille Ephrem; Ahissou, Hyacinthe (Ethnobotany Research and Applications, 2015)
We assessed the diversity, knowledge, and use of antidiabetic plants by traditional healers, plant traders, and farmers from different locations in Benin. Altogether, 254 face-to-face interviews were conducted using a semi-structured questionnaire. Plant diversity was described, based on species richness. Jaccard Index was used to examine the similarity between locations. Consensus values for plant part and manner of use were also computed. A generalized linear model (GLM) with a Poisson distribution was applied to assess the effects of social factors on informants’ knowledge. A total of 203 antidiabetic plant species were mentioned, belonging to 176 genera and 72 families. Predominant used plant parts were leaves, roots, and bark. Main methods of remedy preparations included decoction and infusion. The number of plants mentioned was significantly different among locations (P < 0.05; highest value being found in South Borgou), categories of age (P < 0.05; with adults and older people better informed than youngsters), and types of occupation (P < 0.05; healers reporting more species than farmers and traders). The variation in knowledge among healers, farmers, and traders depended on the location and the category of age. For instance, adult healers disclosed more plants than adult farmers and adult traders, but knowledge of plants was similar either when they were young or old. This study revealed that plants were frequently collected from crop fields and forests, raising concerns of sustainable harvest. It is suggested that home gardens be promoted as tools to reduce pressures on natural forests and prevent medicinal plant erosion.